2014
DOI: 10.4103/0972-124x.138682
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of human papilloma virus in marginal periodontium and its association with periodontitis: A cross sectional study

Abstract: Context:Bacterial pathogens in dental plaque are necessary for the development of periodontitis but this etiology alone does not explain all its clinicopathologic features. Researchers have proven the role of certain viruses like herpes virus in periodontal disease which implies that other viral agents like human papilloma virus may also be involved.Aims:This cross-sectional study was conducted to determine the proportion of patients with human papilloma virus (HPV-16) in marginal periodontium by analyzing DNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 15 publications
(30 reference statements)
0
12
0
Order By: Relevance
“…The oral cavity and oropharynx are lined with various types of specialised epithelia (i.e., mucosal squamous epithelium) [22]. Due to HPV’s known basal cell tropism, it is logical to examine the epithelial components within these regions when studying HPV infections [22].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The oral cavity and oropharynx are lined with various types of specialised epithelia (i.e., mucosal squamous epithelium) [22]. Due to HPV’s known basal cell tropism, it is logical to examine the epithelial components within these regions when studying HPV infections [22].…”
Section: Introductionmentioning
confidence: 99%
“…Due to HPV’s known basal cell tropism, it is logical to examine the epithelial components within these regions when studying HPV infections [22]. Previous studies have shown that self-reported poor oral hygiene is an independent risk factor for high-risk HPV infections [15,23].…”
Section: Introductionmentioning
confidence: 99%
“…In this study, of the total of 90 samples, 38 samples (42.3%) of the samples were found to contain HPV E6/E7 mRNA (0%–2% or >2%), this is in contrast to study by Jacob et al .,[ 18 ] the results obtained showed no HPV was detected in the 102 samples analyzed, where the method of analysis used was PCR.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, HPV DNA has been detected using polymerase chain reaction among other methods. [ 8 17 18 ] However, there is evidence that E6/E7mRNA testing is more specific than DNA testing for HPV detection. [ 19 ] (The HPV genome is composed of three major regions: the long control region, the early genes E1–E8 and late genes L1–L2.…”
Section: Introductionmentioning
confidence: 99%
“…Jacob et al . 13 studying healthy individuals with and without periodontal disease did not find any positive gingival tissue for HPV-16. These results were similar to those obtained by Horewicz et al 14 , with no detection of HPV-16 in either periodontitis or gingivitis.…”
mentioning
confidence: 89%